EXPLORING STUDENTS’ VOICES IN CREATING PODCAST AS PROJECT BASED LEARNING IN SPEAKING CLASS - Syaid Buwono; Surono Surono (IKIP Siliwangi, 2024)
This study aimed to explore student’s voices about using podcasts for their Speaking class project. The participants of this study were 18 students from the fifth semester of the English Education Department at a private university in Yogyakarta. The sampling technique applied is purposive sampling which is based on the specific purposes of this research. The study was conducted through a descriptive qualitative method. The data was collected through open-ended questionnaires to capture the students’ voices on the use of podcasts as a media to fulfill their final project in Speaking class. The results of this study showed that podcasts were effective to use as a media in Speaking class, especially to improve their speaking skills. However, students encountered various challenges, including such as difficulties with editing, fear of making mistakes, limited vocabulary, and pre-production tasks such as topic selection and content arrangement. Despite these challenges, integrating podcasts into Speaking class fostered a positive attitude toward technology adoption, boosted confidence, and enriched students' learning experience.